Protocol-Based Cardiotoxicity Monitoring in Hydroxychloroquine Medicated COVID-19 Pediatric Patients - Hormigo, I (2022)
Introduction/objectives: By May 2020, SARS-CoV-2 had caused more than 400 000 deaths worldwide. Initially, hydroxychloroquine was a treatment option for COVID-19. More recent studies have questioned its safety and efficacy and, until stronger evidence is available, it was suspended from therapy protocols. We describe our experience treating COVID-19 Portuguese pediatric patients with hydroxychloroquine, having applied a protocol for monitoring cardiac toxicity. Methods: An observational retrospective study of COVID-19 pediatric patients, admitted from March to April 2020 and treated with hydroxychloroquine. Cardiotoxicity was assessed using ECG recordings and corrected QT-time (QTc). Patients were classified into risk-groups depending on QTc value: normal, slightly elevated or severely elevated (>500 ms). Results: Total of 14 patients, with a median age of 10 years [four months; 17 years], treated with hydroxychloroquine for a median of five days. Hydroxychloroquine was used in monotherapy in six patients (mainly mild disease with comorbidities), and in association with lopinavir/ritonavir (3) and azithromycin (5) in moderate to severe disease. Other QT-prolonging therapies were used in five patients: oseltamivir (3), omeprazole (1), morphine (1) and ketamine (1). At 48 hours of treatment, two patients temporarily suspended hydroxychloroquine due to QTc prolongation (>500 ms). All patients completed the whole treatment. No other side effects or deaths occurred. Conclusion: Clinical trials are evolving to define hydroxychloroquine effectivity and safety. Our considerable pediatric population supports the need for cardiotoxicity monitoring during therapy but suggest its use seems to be safe in COVID-19 pediatric patients, even in association with other QT-prolonging therapies.